Fenomena Anxiety Politik akibat Ketidakpastian Situasi Politik ditinjau dari Kesehatan Mental - MUHAMMAD ZULFAN AZMI (Scholars, 2025)
The phenomenon of political anxiety is increasing amidst the political instability that is occurring in Indonesia. Uncertainty about government policies, massive disinformation, and sharp political polarization have triggered anxiety that has an impact on individual mental health. This study aims to analyze how political anxiety affects the psychological condition of society by using a literature study approach and analysis of various news sources. Data were obtained from scientific journals, books, and online news that discuss the relationship between political instability and individual anxiety. The results of the study show that political anxiety can trigger chronic stress, social anxiety disorder, and symptoms of depression, especially among vulnerable groups such as the younger generation and individuals with high political exposure. In addition, this condition is exacerbated by the spread of inaccurate news and the inability of individuals to manage information critically. Thus, it is necessary to increase awareness of coping strategies and healthy political literacy in order to reduce the negative impact of political anxiety on people's mental health. Keywords: Political Anxiety, Political Anxiety, Mental Health, Political Instability, Political Stress.